Role of OCT4 in the Regulation of FSH-Induced Granulosa Cells Growth in Female Mice - Heng, Dai; Wang, Qiaozhi; Ma, Xiaoshu; Tian, Ye; Xu, Kaili; Weng, Xuechun; Hu, Xusong; Liu, Wenbo; Zhang, Cheng (Frontiers in Endocrinology, 2020)
As a member of the POU (Pit-Oct-Unc) transcription factor family, OCT4 (Octamer-binding transcription factor 4) is associated with the cellular proliferative. However, the roles of OCT4 in regulating the transition from preantral follicle to early antral follicle are still remains unclear. To evaluate the effect of OCT4 on cellular development in ovary, mice were injected with eCG in vivo or granulosa cells were co-cultured with FSH in vitro. The results showed that eCG up-regulated ovarian OCT4 expression. Meanwhile, OCT4 expression in granulosa cells was also up-regulated by FSH, and knockdown of OCT4 by siRNA significantly decreased FSH-induced cellular viability. Moreover, gonadotropin increased p-GSK3β (Glycogen synthase kinase 3-beta) level, β-catenin expression and its translocation to nuclear in ovarian cells. . In addition, the inhibition of GSK3β activity by CT99021 significantly increased the expression of β-catenin and OCT4 in granulosa cells. And knockdown β-catenin by siRNA dramatically abolished FSH-induced OCT4 expression and cellular development. Furthermore, FSH-induced the phosphorylation of GSK3β, expression of β-catenin and OCT4, and translocation of β-catenin were mediated by the PI3K/Akt pathway. Taken together, the present study demonstrates that FSH regulated OCT4 expression via GSK3β/β-catenin pathway, which was mediated by the PI3K/Akt pathway. And these regulations are involved in ovarian cell development.